Programming logic teaching through abstract problems with plane geometry content (Research, Society and Development, 2022)
This article reports on the application of a workshop with the objective of proposing abstract problems in programming logic based on plane geometry content. The LOGO tool was used for the development of algorithms by students, whose purpose was to build figures from the application of the postulates of plane geometry. These objects were drawn from the turtle's trail, which moves through a sequence of commands from a given algorithm. The results obtained show that there was no direct transfer of knowledge from geometry to the construction of algorithms, but it is necessary to build new knowledge that encompasses these two content domains. We observed difficulties in the interpretation and division of problems and in the capacity for abstraction. We also concluded that we need to focus our pedagogical praxis on activities that develop the students 'abstract thinking, as the area of algorithm programming requires skills with a high level of abstraction and this gap ends up becoming a challenge for the students' development.